Review: Teknologi Biosensor dalam Mendeteksi Senyawa Antidiabetes pada Tanaman - Muhammad Farid Maksum; Nurhaifa Azzahra; Nelis Hernahadini (Jurnal Biodiversitas dan Bioteknologi, 2025)
Type 2 diabetes is a serious, widespread health problem worldwide that causes reduced quality of life, mortality, mortality and significant economic burden. The high number of diabetes sufferers in Indonesia has encouraged the development of anti-diabetic drugs, including those derived from plants used as traditional medicine. The role of biosensors in detecting antidiabetic compounds in plants is very important because they can provide fast, accurate and sensitive methods for biochemical analysis. The purpose of this review is to provide an overview of biosensor technology used for detecting antidiabetic compounds in plant leaves by discussing the general principles of biosensors, their mechanisms using electrochemical biosensor devices, paper-based biosensors, and microzone plastic-based biosensors. The literature study was carried out by searching articles from various leading journal databases, such as PubMed, Google Scholar, and ResearchGate. A review was carried out regarding biosensor devices as anti-diabetic compound detectors with three technical types, namely electrochemical, paperbased and microzone plastic-based. Based on sensitivity and other advantages, microzone plastic-based biosensors are the best biosensors compared to the other two biosensors. The use of microzone plastic-based biosensors is also very simple, requiring only the placement of the sample on the detection area, after which the compound can be detected through the scanner/sensor features embedded in the device